The effect of augmented reality application (ARSINAPS) on learning motivation and outcomes in biology - Rini, Daniar Setyo; Azrai, Eka Putri; Khansa , Anidya Annisa; Kurnianto, Mathias Bagas (Biosfer: Jurnal Pendidikan Biologi, 2024)
This study aims to determine the effectiveness of using the ARSINAPS mobile augmented reality application on learning motivation and outcomes in high school and biology education students. The method used in this study was quasi-experimental with a post-test control group design. The research sample consisted of two experimental classes and two control classes from three schools in the Jakarta, Bekasi, and Tangerang areas, totalling 140 students, and from the college level, consisting of one experimental class and one control class, totalling 68 students. The data obtained were in the form of learning outcomes in the respiratory system and learning motivation scores in biology learning. The average high school-level motivation score in the control class was 85.99, and the overall average for learning outcomes was 77.33 and 63.05. Based on the results of the data calculations, the application effectively improves students’ learning outcomes at the high school and undergraduate levels